Evidence of spotted fever group rickettsiae in state of Rio de Janeiro, Brazil - ROZENTAL, Tatiana; BUSTAMANTE, Maria Cristina; AMORIM, Marinete; SERRA-FREIRE, Nicolau Maués; LEMOS, Elba Regina Sampaio de (Revista do Instituto de Medicina Tropical de São Paulo, 2002)
Ticks were obtained from dogs from February to September of 1999 at weekly intervals, in the County of Piraí, State of Rio de Janeiro. Four hundred seventy four ixodids were taxonomically identified, 103 Amblyomma cajennense, seven Amblyomma ovale, 209 Rhipicephalus sanguineus, and 155 Amblyomma sp. An hemolymph test associated with Giemsa's stain revealed two specimens in 163 ticks tested (R. sanguineus and Amblyomma sp), containing rickettsia-like organisms. Direct immunofluorescence verified the presence of spotted fever group rickettsia in one specimen of R. sanguineus. Considering the limited information on rickettsiosis in Brazil, principally in relation to the vectors involved in perpetuating it in foci, these preliminary results give us an idea on the importance of infection in ticks, allowing to expand our knowledge on this zoonosis.